DAKWAH ISLAMIYAH: MENIMBANG KEMBALI KONSEP DAKWAH ISLAM MOHAMMAD NATSIR - Akhmad Anwar Dani (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Basically, Islam is message (risalah) religion that it put its da’wah activities in delivering all doctrines which are consist inside this religion. These become center role for developing the future. Da’wah vitality in Islam gives the signal that will come the new formulation appropriating with developing of the world in this time. It is an opportunity for Islam in order it’s doctrines concept were received by new civilization; modern civilization. This proposition will be answered by Muhammad Natsir with amarma’ruf nahi munkar concept, which it combined the matter of da’wah, subject of da’wah and object of da’wah as a concept inseparable between and other.